2012
DOI: 10.3174/ajnr.a3248
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Reconstruction for Treatment of Vertebrobasilar Dolichoectasia: Long-Term Outcomes

Abstract: BACKGROUND AND PURPOSE: VBD can trigger various clinical symptoms, especially ischemic stroke in the posterior circulation, but there is no effective treatment for their prevention. We aimed to validate the feasibility of coil-assisted stent reconstruction in the vascular lumen for the treatment of VBD and to evaluate its long-term effectiveness in preventing ischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 40 publications
0
45
0
1
Order By: Relevance
“…Before the prevalence of PED and SFD, overlapping stent or coil-assisted stent reconstruction may be a valuable alternative71-76, Cohen et al 73 used four Leo stents and one SFD with the overlapping stent releasing technology to block the blood supply to the vertebral artery and successfully cured a VBD patient. In spite of the initial neurological dysfunction, the patient gradually recovered well.…”
Section: Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the prevalence of PED and SFD, overlapping stent or coil-assisted stent reconstruction may be a valuable alternative71-76, Cohen et al 73 used four Leo stents and one SFD with the overlapping stent releasing technology to block the blood supply to the vertebral artery and successfully cured a VBD patient. In spite of the initial neurological dysfunction, the patient gradually recovered well.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…If formation of blood stasis or straightening of tortuous blood vessels is not sufficient, implantation of SFD is required and occlusion of dominant arteries can be applied if necessary. Wu et al 71 used coil-assisted stent reconstruction in the treatment of 9 patients with symptomatic VBD. One patient died from brain stem infarction and one patient developed paralysis due to brain stem infarction after 1 month.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…There is no systematic large-scale study for the treatment of VBD by drugs, surgery or interventional operation and a lack of large-scale randomized controlled trials for anticoagulation and antiplatelet therapy [2]. Endovascular reconstruction of vertebrobasilar vessels can be another choice [16]. In our case we could not use the surgical or endovascular therapy, we could use anticoagulation and antiplatelet therapy alone.…”
Section: Journal Of Neurology and Neurosciencementioning
confidence: 99%
“…The authors supported microsurgery as a safe and more durable treatment option for the management of complex basilar apex aneurysms that tend to have a higher rate of failure with endovascular therapy 17 . Wu et al 11 aimed to validate the feasibility of coil-assisted stent reconstruction in the vascular lumen for the treatment of VBD and to evaluate its long-term effectiveness in preventing ischemic events. They found that endovascular reconstruction with coil-assisted stent placement or stent placement alone in the vascular lumen for the treatment of VBD is technically feasible and can prevent ischemic events in the territory of stented vessels compared with the natural course, though further studies in larger samples are needed 11 .…”
Section: Posterior Circulationmentioning
confidence: 99%
“…A giant VBD with only slight compressive symptoms is unusual 9 . Further, VBD can trigger various clinical symptoms such as posterior circulation stroke (including ischemia of cervical spine, cerebellum and cerebral trunk, as well as occipital lobe syndromes), cranial nerve palsies, subarachnoid or intracerebral haemorrhages and even symptoms of a neoplasm in the posterior fossa and in the cerebellopontine angle, but there is no effective treatment for their prevention [9][10][11][12] . The clinical symptom that should be stressed is headache, which precedes the occurrence of stroke for several days 12 .…”
Section: Introductionmentioning
confidence: 99%